Share to Survive - Spanbroek, Nancy (1999)
Where competition is fierce and occurring on a global level, the designer must be armed with all the tools necessary to survive, this includes up to date information, skills and resources. Schon recommends collaboration between researchers and practitioners to publish their experiences and findings on design projects (Schon, 1988). Unless practitioners share information and build up on a resource of knowledge they will leave themselves open to further fragmentation of their profession. They will dissipate into a meaningless superficial body of designers that are not taken seriously. This paper discusses why professional interior designers are reluctant to share information and enter design discourse.